EVALUASI KINERJA PEMERINTAH DAERAH KOTA PEKANBARU DALAM MENGELOLA PAJAK AIR TANAH TAHUN 2018 - Lisa Amelia; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study discusses how to evaluation the performance of the Pekanbaru City Government in managing the ground water tax in this case the Pekanbaru City Revenue Agency as a revenue support function. The purpose of this study is to find out how to evaluation the performance of the Pekanbaru City Government in managing ground water taxation and inhibiting factors evaluation the performance of the Pekanbaru City Government in managing groundwater tax.The theoretical concept used in the study is performance evaluation with input, output and outcome indicators. This study uses qualitative research methods, with descriptive data review. In collecting data, researchers used interview, observation, and documentation techniques.The study showed that the evaluation of the performance of the Pekanbaru City Government in managing ground water tax was not optimal. This is evidenced by the unachievement of the ground water tax target each year and is caused by the lack of seriousness of the Pekanbaru City Government in managing this ground water tax. However, there are also inhibiting factors that affect the performance of local governments in managing ground water taxes, namely the lack of staff, inadequate facilities and infrastructure, and the lack of community participation. Keywords: Performance Evaluation, Groundwater Tax